Stable and Potent Selenomab-Drug Conjugates. Issue 4 (20th April 2017) - Li, Xiuling; Nelson, Christopher G.; Nair, Rajesh R.; Hazlehurst, Lori; Moroni, Tina; Martinez-Acedo, Pablo; Nanna, Alex R.; Hymel, David; Burke, Terrence R.; Rader, Christoph
Summary: Selenomabs are engineered monoclonal antibodies with one or more translationally incorporated selenocysteine residues. The unique reactivity of the selenol group of selenocysteine permits site-specific conjugation of drugs. Compared with other natural and unnatural amino acid and carbohydrate residues that have been used for the generation of site-specific antibody-drug conjugates, selenocysteine is particularly reactive, permitting fast, single-step, and efficient reactions under near physiological conditions. Using a tailored conjugation chemistry, we generated highly stable selenomab-drug conjugates and demonstrated their potency and selectivity in vitro and in vivo. These site-specific antibody-drug conjugates built on a selenocysteine interface revealed broad therapeutic utility in liquid and solid malignancy models. Graphical Abstract: Highlights: Selenomab-drug conjugates are antibody-drug conjugates based on selenocysteine Iodoacetamide-based selenomab-drug conjugates have excellent stability Selenomab-drug conjugates are potent and specific cancer therapeutics The location of selenocysteine in selenomab-drug conjugates impacts their potency Abstract : Li et al. harness the high reactivity of the 21 st natural amino acid selenocysteine to rapidly and efficiently assemble antibody-drug conjugates that reveal excellent stability, potency, and selectivity in diverse in vitro and in vivo models of human cancers.